Preparation of Ampicillin-derived CQDs and its Application in the Detection of Phenols in Medicinal Materials - Zhang, Yu; Zhang, Ping (Current Nanoscience, 2024)
Background: In this study, ampicillin sodium fluorescent carbon quantum dots were prepared by one-step hydrothermal method with ampicillin sodium as the carbon source and urea as the nitrogen source. Methods: The structure of CQDs were characterized by UV-Vis and fluorescence spectrophotometer. The pH, reaction time and ionic strength of phenol detected by N-CQDs were optimized. The optimum experimental conditions were 40 μL ampicillin sodium N-CQDs, 2 mL buffer solution with pH 8.0, and the reaction time was 6 min. Results: Through the detection of fluorescence spectrophotometry, p-nitrophenol had obvious fluorescence quenching phenomenon on ampicillin sodium N-CQDs, and the detection limit was 75 nM. It was used in the standard addition experiment of actual samples, and the recovery rates were more than 85%. Conclusion: Therefore, the N-CQDs could be used as fluorescent probe to analyze the content of p-nitrophenol in the actual environment.
Keywords: p-nitrophenol